Pengaruh Karakteristik Individu Dan Kepuasan Kerja Terhadap Kinerja Karyawan - Zulkarnain Mora; Syardiansah syardiansah; Ikhsan Ari Mufti (Universitas Negeri Medan, 2021)
This study was conducted to determine the effect of individual characteristics and job satisfaction onemployee performance at the Cut Meutia Hospital, Langsa City. The sample in this study amounted to 86respondents. The data analysis method used is multiple linear regression analysis, hypothesis testing usingt test, F test, and determination test (R2). The results showed that Y = 0.895 + 0.151X1 + 0.805X2. The resultsof the t test for individual characteristics sig <α 5% (0.019 <0.05), it can be stated that individualcharacteristics have a significant effect on the performance of the employees of Cut Meutia Hospital, LangsaCity. The results of the t test job satisfaction t sig <α 5% (0,000 <0.05) can be stated that job satisfaction hasa significant effect on the performance of the employees of Cut Meutia Hospital, Langsa City. The results ofthe F test are known from F sig <α 5% (0,000 <0.05), it can be stated that individual characteristics and jobsatisfaction simultaneously have a significant effect on the performance of the employees of Cut MeutiaHospital, Langsa City. The results of the coefficient of determination (R2) obtained results of 0.737 or 73.7%of individual characteristics and job satisfaction affect the performance of employees at Cut Meutia Hospital,Langsa City and the remaining 26.3% is influenced by other variables.